A mind you can count on: validating breath counting as a behavioral measure of mindfulness - Levinson, Daniel B.; Stoll, Eli L.; Kindy, Sonam D.; Merry, Hillary L.; Davidson, Richard J. (Frontiers in Psychology, 2014)
Mindfulness practice of present moment awareness promises many benefits, but has eluded rigorous behavioral measurement. To date, research has relied on self-reported mindfulness or heterogeneous mindfulness trainings to infer skillful mindfulness practice and its effects. In four independent studies with over 400 total participants, we present the first construct validation of a behavioral measure of mindfulness, breath counting. We found it was reliable, correlated with self-reported mindfulness, differentiated long-term meditators from age-matched controls, and was distinct from sustained attention and working memory measures. In addition, we employed breath counting to test the nomological network of mindfulness. As theorized, we found skill in breath counting associated with more meta-awareness, less mind wandering, better mood, and greater nonattachment (i.e. less attentional capture by distractors formerly paired with reward). We also found in a randomized online training study that 4 weeks of breath counting training improved mindfulness and decreased mind wandering relative to working memory training and no training controls. Together, these findings provide the first evidence for breath counting as a behavioral measure of mindfulness.